A comparative study of Emotional Quotient with relation to Blood Groups among medical students of Punjab - Rida Naseer Ghouri, Muhammad Ehtisham, Shireen Jawed, (Journal of Rawalpindi Medical College, 2022)
Introduction: Emotional quotient (EQ) is the ability to monitor one’s own and other's feelings and emotions for managing relations appropriately. It implies critical thinking and has a key role in augmenting coherence between the team members to work at their full potential for achieving their goals and success in life. There are numerous lines of evidence that shows the influence of blood groups on skills and abilities related to EQ. Individuals with blood group B are active and passionate but those with blood group A are intelligent, loyal to their work, and have maudlin behavior. People with AB blood group are spiritual and O blood groupers have leadership character and least respond to stress. This study aims to compare the EQ-related skills and abilities among medical students with various blood groups. Materials and Methods: A cross-sectional study was conducted at Aziz Fatimah medical and dental college, Faisalabad. Validate proforma consisting of questions related to demographic, blood groups, and Emotional intelligence scale (EIS) for EQ-related questions was constructed on google form and the link was shared among 600 MBBS students of different medical colleges in Punjab, Pakistan. Only 566 students filled out complete proforma and fulfilled our inclusion criteria for enrollment in the study. Data were retrieved from the individual responses of google form and transformed on SPSS 22 for data analysis. P values less ≤ than 0.05 were considered significant. Results: The most frequent blood group was B positive (B+ve) in this study. The highest score concerning self-awareness was in blood group A positive (A+ve) followed by O positive (O+ve) with a P-value=0.017. The highest score was observed in B+ve in the case of empathy but the difference in mean score was not statistically significant (p value= 0.326). Similarly, blood group A+ve showed the highest value in self-motivation, emotional stability, and managing relations with P-values of 0.036, 0.005, and 0.046 respectively. Participants with the A+ve blood group were more value-oriented, committed, showed integrity and altruistic behavior with P-value=0.032, 0.000, 0.013, and 0.032 respectively. Conclusion: People with the blood group A+ve had the highest emotional quotient than other blood groups. Blood group B was the most prevalent blood group in our study population.